The Concept Of The Needs Of Society According To Abraham Maslow's perspective - Andarweni Astuti; Loina Christine (Jurnal Bimbingan dan Konseling Indonesia, 2022)
This research has the background of the human tendency to satisfy the needs of their lives to the highest level, but the level of satisfaction of each individual is different as evidenced by research on private employees in Kampung Batik Semarang. The purpose of this study is to find an overview of the views of employees about the concept of their life needs. The focus of this research is to describe Abraham Maslow's hierarchy of needs for employees. The method used is qualitative research. The finding is that most of the employees have been able to fulfill physiological needs, safety needs, social needs, and also esteem needs, but in terms of self-actualization needs, they have not been met, as evidenced by the results of interviews that 75% of them said that line needs this last one has not been fulfilled.